2007
DOI: 10.1243/09544070jauto211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of military JP-8 fuel on heavy-duty diesel engine performance and emissions

Abstract: Investigating the impact of jet fuel on diesel engine performance and emissions is very important for military vehicles, due to the US Army Single Fuel Forward Policy mandating that deployed vehicles must refuel with aviation fuel JP-8. There is a known torque and fuel economy penalty associated with the operation of a diesel engine with JP-8 fuel, due to its lower density and viscosity. On the other hand, a few experimental studies have suggested that kerosene-based fuels have the potential for lowering exhau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 6 publications
1
53
0
Order By: Relevance
“…Analysis of the needle-valve lifts and in-cylinder heat release characteristics shows that the replacement of the diesel fuel by commercial aviation fuel F-34 leads to the autoignition delay longer over all loads and speeds than that of the normal diesel. Such autoignition delay behaviour matches pretty well with the test results of commercial JP-8 aviation fuel, which is comparable with military F-34 fuel, on various types of DI diesel engines obtained by other researchers [3,5,6].…”
Section: Tab 1 Properties Of Diesel Fuel (Grade C) and Jet Fuel (Nasupporting
confidence: 89%
See 1 more Smart Citation
“…Analysis of the needle-valve lifts and in-cylinder heat release characteristics shows that the replacement of the diesel fuel by commercial aviation fuel F-34 leads to the autoignition delay longer over all loads and speeds than that of the normal diesel. Such autoignition delay behaviour matches pretty well with the test results of commercial JP-8 aviation fuel, which is comparable with military F-34 fuel, on various types of DI diesel engines obtained by other researchers [3,5,6].…”
Section: Tab 1 Properties Of Diesel Fuel (Grade C) and Jet Fuel (Nasupporting
confidence: 89%
“…The lower cetane number of JP-8 cause an increased ignition delay and increased premixed combustion, and their cumulative effect led to relatively unchanged combustion phasing. Under almost all conditions, JP-8 led to lower NO x and PM emissions and shifted the NO x -PM trade-off favourably [6].…”
Section: Introductionmentioning
confidence: 97%
“…and a wider spray angle improved atomisation and the air and jet fuel vapours mixing rate [14,15]. The tests conducted on a Detroit Diesel Corporation (DDC) military, heavy-duty S60 engine outfitted with EGR showed that under almost all conditions, the NO x emissions and particle matters decrease and the NO x -PM trade-off shifts favourably when running with JP-8 fuel [16]. This happened because of a higher mixing rate of the air and jet fuel vapours and smoother temperature variation in the combustion chamber.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results presented in reference [8], it is possible to match the performance of the engine with a D2 fuel to that of a JP-8 fuel by engine calibration. Moreover, according to reference [8], brake-specific fuel consumption (BSFC) values of both fuels are very close when the performance is matched. It can therefore be concluded that results for diesel fuel D2 is representative for kerosene-based fuels and other heavy fuels.…”
Section: Description Of the Enginementioning
confidence: 99%